2019
DOI: 10.1038/s41419-019-2170-4
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 promotes tumor progression and NF-κB/CCL2-dependent tumor-associated macrophage recruitment in GIST

Abstract: The most commonly occurring sarcoma of the soft tissue is gastrointestinal stromal tumor (GIST). Treatment and prevention of the disease necessitate an understanding of the molecular mechanisms involved. However, the role of BRD4 in the progression of GIST is still unclear. While it is known there are abundant infiltrating tumor-associated macrophages (TAMs) in the tumor microenvironment, the exact role of these cells has yet to be studied. This work showed an upregulation of BRD4 in GIST that was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
(45 reference statements)
1
28
0
Order By: Relevance
“…BRD4 has been documented to activate NF-κB pathway in gastrointestinal stromal tumor [29]. The inhibition of NF-κB is positively associated with the inhibition of vascular disease development, including PE [30].…”
Section: Discussionmentioning
confidence: 99%
“…BRD4 has been documented to activate NF-κB pathway in gastrointestinal stromal tumor [29]. The inhibition of NF-κB is positively associated with the inhibition of vascular disease development, including PE [30].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcomas are also frequently infiltrated by macrophages, which represent the main immune infiltrate and a highly heterogeneous population (Toulmonde et al , 2018; Mu et al , 2019; Stahl et al , 2019). Macrophage subpopulations are composed of a balance between immune‐stimulatory M1 and immune‐suppressive M2 macrophages that can be dysregulated in sarcomas.…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…Studies have shown that SPOP can mediate the degradation of BRD4 [ 36 , 37 ]. On the one hand, in SPOP-deficient PCa cells, enhanced BRD4 transcription co-activation and increased ERG expression jointly promoted cell migration.…”
Section: Discussionmentioning
confidence: 99%